Hydropic degeneration of leiomyoma in nongravid uterus: The “split fiber” sign on magnetic resonance imaging - Patil, Aruna R. (Indian J Radiol Imaging, 2018)
Extensive hydropic degeneration in uterine leiomyoma is a rare occurrence and is commonly reported in association with pregnancy. It is a close mimicker of malignancy due to rapid growth and atypical imaging appearances. Awareness of the imaging features helps in diagnosis, avoids unnecessary patient anxiety, and hence reassurance especially when encountered in pregnancy. We report two cases of extensive hydropic degeneration of leiomyoma in nonpregnant females with imaging and histopathology correlation. We also propose the “split fiber” sign as a useful magnetic resonance imaging feature for diagnosing this condition.